"Black Snakes": Identification and Ecology - Steve A. Johnson; Monica E. McGarrity (EDIS)
WEC-214, a 7-page color illustrated fact sheet by Steve A. Johnson and Monica E. McGarrity, describes several species of black-colored snakes found in the southeastern U.S., the habitats they occur in and some identifying features. The Eastern Indigo Snake and Southern Black Racer are given special consideration. Published by the UF Department of Wildlife Ecology and Conservation, November 2006.